EFFECTIVENESS TEACHER-CENTERED METHOD OF TEACHING CHRISTIAN RELIGIOUS EDUCATION IN INSTILLING RESPECT AMONG STUDENTS IN PUBLIC SECONDARY SCHOOLS IN RACHUONYO NORTH SUB-COUNTY, KENYA - Otieno, Wachiaji Anton Peter (African Journal of Education and Practice, 2021)
Purpose: This study evaluated the effectiveness of teacher-centered method of teaching Christian Religious Education in instilling respect among students in public secondary schools in Rachuonyo North Sub-County, Kenya. Methodology: The study was guided by the Bandura's social learning theory. A descriptive survey design was adopted. The study population comprised 50 CRE teachers and 1,615 Form Four students taking CRE in 49 public secondary schools. Simple random sampling technique was used to select 15 teachers, and 485 Form Four students from the accessible population. Face to face interviews were conducted to collect data from teachers while questionnaires were administered to collect data from students. Quantitative data from questionnaire were analyzed with the aid of Statistical Package for Social Sciences (SPSS) Version 20.0 using descriptive statistics as well as inferential statistics and presented in tabular form. Data from interviews was analyzed qualitatively and presentation was done in narrative form. Findings: Majority of the interviewed students were male and were in the age category of 17-21 years of age while nearly two thirds of the interviewed teachers were males with different levels of education ranging from bachelors to PhD. Majority of the students reported that the use of school assignments, lectures, homework, game based approach, mental modeling approach, classroom instructions, and role play enhanced acquisition of virtue of respect. The Pearson's product moment correlation coefficient showed that there existed a positive, strong and statistically significant association between teacher-centered methods and instilling virtue of respect in students (r = 0.876; p < 0.05). Contribution to theory, practice and policy: The study concludes that strategic use of classroom approach through assignments, homework, and talk's is essential in acquisition of virtue of respect among students. Furthermore, teacher-centered methods play critical roles in instilling the virtue of respect among students. Therefore, teachers should be assisted to acquire competence in correct C.R.E syllabus interpretation in order to enable them to adapt varied methods of teaching, policies should ensure systematic implementation of inclusive teaching methods for every student and creation of knowledge on teacher centered teaching methods.